2020
DOI: 10.3389/fphar.2020.00042
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Types of Cell Death and the Implication in Diabetic Cardiomyopathy

Abstract: Diabetic cardiomyopathy (DCM) is a chronic complication of diabetes mellitus, characterized by abnormalities of myocardial structure and function. Researches on the models of type 1 and type 2 diabetes mellitus as well as the application of genetic engineering technology help in understanding the molecular mechanism of DCM. DCM has multiple hallmarks, including hyperglycemia, insulin resistance, increased free radical production, lipid peroxidation, mitochondrial dysfunction, endothelial dysfunction, and cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
111
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(111 citation statements)
references
References 94 publications
0
111
0
Order By: Relevance
“…103 Growing evidence reports that DCM is closely related to pyroptosis associated with inflammation. 104,105 Pyroptosis-regulated cell death plays a significant role in DCM development. Previous research has documented that pyroptosis-related proteins, including GSDMD, caspase-1, NLRP3 inflammasome, and IL-1β expression levels are augmented in cardiac tissues.…”
Section: Diabetic Cardiomyopathymentioning
confidence: 99%
“…103 Growing evidence reports that DCM is closely related to pyroptosis associated with inflammation. 104,105 Pyroptosis-regulated cell death plays a significant role in DCM development. Previous research has documented that pyroptosis-related proteins, including GSDMD, caspase-1, NLRP3 inflammasome, and IL-1β expression levels are augmented in cardiac tissues.…”
Section: Diabetic Cardiomyopathymentioning
confidence: 99%
“…Oxidative stress, which can interfere the balance between antioxidant capacity and the production of ROS, has been widely accepted as a common mechanism of DCM ( Khullar et al, 2010 ; Huynh et al, 2014 ). Considering that ROS formation promotes ferroptosis, it is very likely that ferroptosis is involved in DCM ( Anandhan et al, 2020 ; Chen et al, 2020 ). Zang et al (2020) showed that diabetes was capable of inducing autophagy deficiency with time, resulting in Nuclear factor-erythroid factor 2-related factor 2 (Nrf2)-mediated defense was turned off.…”
Section: The Role Of Ferroptosis In Cardiomyopathymentioning
confidence: 99%
“…( Guiney et al, 2017 ; Stockwell et al, 2017 ). Recently, several studies have demonstrated that ferroptosis played a crucial role in myocardial homeostasis and pathology ( Akazawa, 2015 ; Conrad and Proneth, 2019 ; Chen et al, 2020 ; Li W. et al, 2020 ). However, the biological roles and regulation pathways of ferroptosis in cardiovascular diseases have not been entirely understood.…”
Section: Introductionmentioning
confidence: 99%
“…The circadian rhythm is an endogenous mechanism that controls various cellular processes such as iron metabolism, oxidative stress, and cell death [53]. It is obvious that several mechanisms can act together in the same pathology or process and, also, the opposite, that several pathologies share the same mechanism [54][55][56][57]. Immunogenic cell death (ICD) is a functionally peculiar form of RCD that is sufficient to activate an adaptive immune response specific for endogenous (cellular) or exogenous (viral) antigens expressed by dying cells.…”
Section: Ferroptosismentioning
confidence: 99%